The Mestizo State : Reading Race in Modern Mexico. - Lund, Joshua (University of Minnesota Press, 2012)
The Mestizo State examines how the ideas, images, and public discourse around race, nation, and citizen formation have been transformed in Mexico from the mid-nineteenth century to the present. Starting with the Porfiriato, Joshua Lund investigates the rise of a racialized "mestizo state," its reinvention after the Mexican Revolution, and its mobilization as a critical lever that would act both on behalf of and against mainstream Mexican political culture during the long hegemony of the Partido Revolucionario Institucional. Lund takes race as his object of critical reflection in the context of.